2022
DOI: 10.1111/lam.13783
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of probiotic Bifidobacterium isolated from chicken's intestine in combination with polyvinylpyrrolidone on reduction of aflatoxin B1

Abstract: Significance and Impact of the Study: Although various technologies (physical, chemical and biological) have been investigated to reduce the adverse effects of aflatoxins, these efforts have not yet resulted in a cost-effective, general toxin binder to eliminate or reduce aflatoxins. The present study results show that Bifidobacterium bifidum, a native probiotic isolated from chick's intestines in combination with PVP polymer, has a high ability (up to 90%) in removing AFB 1 from MRS medium and, therefore, can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the chicken gastrointestinal tract is regarded as an excellent area for screening more strains with significant probiotic characteristics. Aalipanah et al reported that a strain of B.bifidum isolated from the chicken intestine showed potential probiotic characterization [37]. A strain of B. dentium from chicken intestines was isolated by Palacios et al, exhibiting the highest phytase activity [38].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the chicken gastrointestinal tract is regarded as an excellent area for screening more strains with significant probiotic characteristics. Aalipanah et al reported that a strain of B.bifidum isolated from the chicken intestine showed potential probiotic characterization [37]. A strain of B. dentium from chicken intestines was isolated by Palacios et al, exhibiting the highest phytase activity [38].…”
Section: Plos Onementioning
confidence: 99%
“…The determination of antimicrobial activity is a necessary step in the screening process of Bifidobacterium [74,75]. Aalipanah et al [37] used disk diffusion method to evaluate the antibacterial property of B. bifidum strain originated from chicken intestinal tract, which had antibacterial property against E. coli. Jang et al [62] reported that B. longum CACC517 isolated from dog feces showed antibacterial activity against S. enteritidis and E. coli.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation